The gravity model for Maltese goods exports and imports - Reuben Ellul (Central Bank of Malta, 2019)
Malta's path of economic development benefited from international trade, as the country is situated on trade routes linking Europe, Africa and Asia. This paper aims to look at the country's location, trade agreements, cultural attributes and size in a gravity model framework. Its almost 50 year old relationship with the EU and its precursors, coupled with its strategic location, led to extraordinary growth rates in trade in goods between 1960 and 2016. The various versions of the gravity model applied here suggest strong and significant impacts of successive trade agreements with the European continent for both exports and imports. This is looked at using nominal, real and sectoral data.
Keywords: C23; F1; F14; F15; 330